Microbial dysbiosis in melasma through community profiling - Reddy B.S, Yugandhar; Doraiswamy, Chandraprabha; Singh, Deepshikha; Surendra, Nagalakshmi; Damle, Aparna; Dutta, Maitreyee; Rajkumar, Savitha; Potterf, Brian; Roy, Arindam; Cheviti, Bharat; Dadd, Tony; Arnold, David; et al. (Frontiers in Microbiomes, 2025)
BackgroundThe complex ecosystem on skin comprising tens of thousands of microorganisms plays an important role in health and disease. The last decade in particular has witnessed a surge in microbiome research, which has been elucidating the role of the microbiota in numerous skin pathologies. Of relevance to the current study, are recent evidences implicating the microbiome in skin pigmentary conditions. Melasma is one such refractory, hyperpigmentary condition with a poorly understood pathogenesis. The present study was carried out to characterize the nature of microbial dysbiosis and its impact on microbial community structure in melasma subjects.ResultsThe clinical assessment of melasma carried out using biophysical, biochemical and biomarker-based measures confirmed significant changes in melasma lesions, most notably, those linked to redox, inflammation and barrier properties. A deep characterization of the skin microbiome in melasma from human face, indicated significant differences between lesional and peri-lesional areas. Of the 377 genera identified through an agglomeration of all OTUs at the Genus level through 16S rRNA sequencing, 344 were common, while 12 were unique to lesional and 21 unique in peri-lesional areas. A significant decrease was observed in alpha diversity in melasma lesion as compared to peri-lesion areas, with an accompanying decrease in number of interconnections among them. The differences in the microbiome also appeared to correlate with several clinical parameters, notably with the melasma severity measured through modified MASI (mMASI) scoring. The observed changes in both host and microbiome, point to a potential role for the latter in melasma pathogenesis.ConclusionsOur study indicates that there are significant differences in the microbiome between lesional and peri-lesional areas of melasma subjects, with associated changes in microbial community structures. Additionally, the observed changes were seen to correlate with measured clinical parameters. These findings provide the opportunity to further probe the nature of host and microbiome links that may underlie the phenotypic manifestation, as well as provide effective routes for managing this recalcitrant disorder.